Legal Resolution for the Failure to Meet the 30% Representation of Women in the Bintan Regency DPRD Election through the State Administrative Court and the District Court - Yuhendra Tanjung; Medianto Medianto (Center for Maritime Policy Governance Studies (CMPGS), 2026)
This article examines legal certainty in the dispute resolution of the 30 percent women’s representation requirement in the Bintan Regency DPRD election. The issue arises from an electoral dispute concerning the alleged non-fulfillment of the minimum women’s representation requirement in the candidate list of a political party in Bintan Electoral District 3, where the proportion of women candidates was argued to be below the statutory threshold. This case is significant because it reflects the tension between affirmative action in electoral politics and the procedural certainty required in election dispute resolution. The objective of this study is to analyze how legal certainty operates in resolving disputes over women’s representation, particularly in relation to institutional jurisdiction, procedural deadlines, the finality of election results, and the validity of election management decisions. This study employs a qualitative juridical-normative method using secondary data obtained from statutory regulations, KPU decisions, Constitutional Court decisions, DKPP decisions, official election documents, and relevant scholarly literature. The findings show that the 30 percent women’s representation requirement is a binding affirmative electoral norm intended to strengthen inclusive democracy and gender equality. However, its enforcement must follow the correct legal stage and institutional mechanism. In the Bintan case, the dispute was submitted after the formal determination of election results, thereby raising questions regarding judicial competence and procedural admissibility. The study also finds that the principle of praesumptio iustae causa confirms the validity of KPU decisions until annulled by a competent authority. The article concludes that gender-responsive electoral justice must be integrated with legal certainty through early verification, preventive supervision, clear dispute pathways, legal education for electoral participants, and consistent institutional coordination.